GeneXpert or chest-X-ray or tuberculin skin testing for household contact assessment (GXT): protocol for a cluster-randomized trial - AFFOLABI, DISSOU (My University, 2022)
Background: The World Health Organization recommends tuberculosis (TB) preventive treatment (TPT) for all people living with HIV (PLH) and household contacts (HHC) of index TB patients. Tests for TB infection (TBI) or to rule out TB disease (TBD) are preferred, but if not available, this should not be a barrier if access to these tests is limited for high-risk people, such as PLH and HHC under 5 years old. There is equipoise on the need for these tests in different risk populations, especially HHC aged over 5. Methods: This superiority cluster-randomized multicenter trial with three arms of equal size compares, in Benin and Brazil, three strategies for HHC investigation aged 0-50: (i) tuberculin skin testing (TST) or interferon gamma release assay (IGRA) for TBI and if positive, chest X-Ray (CXR) to rule out TBD in persons with positive TST or IGRA; (ii) same as (i) but GeneXpert (GX) replaces CXR; and (iii) no TBI testing. CXR for all; if CXR is normal, TPT is recommended. All strategies start with symptom screening. Clusters are defined as HHC members of the same index patients with newly diagnosed pulmonary TBD. The main outcome is the proportion of HHC that are TPT eligible who start TPT within 3 months of the index TB patient starting TBD treatment. Societal costs, incidence of severe adverse events, and prevalence of TBD are among secondary outcomes. Stratified analyses by age (under versus over 5) and by index patient microbiological status will be conducted. All participants provide signed informed consent. The study was approved by the Research Ethic Board of the Research Institute of the McGill University Health Centre, the Brazilian National Ethical Board CONEP, and the "Comité Local d'Éthique Pour la Recherche Biomédicale (CLERB) de l'Université de Parakou," Benin. Findings will be submitted for publication in major medical journals and presented in conferences, to WHO and National and municipal TB programs of the involved countries. Discussion: This randomized trial is meant to provide high-quality evidence to inform WHO recommendations on investigation of household contacts, as currently these are based on very low-quality evidence. Trial registration: ClinicalTrials.gov NCT04528823. Keywords: Cascade of care; Chest X-ray; GeneXpert; Household contacts; Latent tuberculosis; Tuberculin skin testing.
Keywords: Keywords: Cascade of care; Chest X-ray; GeneXpert; Household contacts; Latent tuberculosis; Tuberculin skin testing.